Possibilities of peripheral magnetic neuromodulation in the treatment of lower urinary tract symptoms in men - I. A. Labetov; G. V. Kovalev; A. S. Shulgin; N. D. Kubin; D. D. Shkarupa (Вестник урологии)
Introduction. Lower urinary tract symptoms (LUTS) are common in men and are associated with a significant decrease in quality of life. To date, there is no universal approach to the treatment of LUTS, which determines the need to search for new methods for influencing the lower urinary tract.Purpose of the study. To test the hypothesis that the use of peripheral magnetic neuromodulation (PMN) in male patients with LUTS will reduce the severity of LUTS.Materials and methods. Sixty-eight men with LUTS were enrolled in a prospective, randomized study. Patients were randomized in a 1:1 ratio for PMN or drug therapy with an alpha-1-blocker (tamsulosin). The primary endpoint was a reduction the LUTS severity such as urinary frequency during the day, nocturia and urgency as assessed using the IPSS questionnaire and urination diary. Improvements in urodynamic parameters such as maximum urine flow rate (Q max), mean urine flow rate (Q ave), and residual urine volume (PVR) were the secondary endpoint of the study. The results were evaluated on equal terms (10 days and 1 month) in both groups.Results. Sixty-seven (98.5%) subjects were included in the final base. Ten days after the start of therapy in the magnetic stimulation group, symptom relief was noted by 21 people (61.7%), the mean IPSS score showed a decrease from 18.1 ± 2.1 to 16.9 ± 3.2 points (p = 0.037). The number of urinations per day decreased from 14 (6 - 20) to 10 (6 - 14) times (p < 0.001). Objective indicators of urodynamics did not change in both groups. At a period of 1 month, PMN occurred in 22 (64.7%) patients, the IPSS score was 16.6 ± 3.7 points (p = 0.032), the number of urinations 9 (6 - 14) times (p < 0.001). Objective indicators have not changed. In the tamsulosin group, IPSS score changed from 19.27 ± 5.08 to 15.4 ± 4.85 (p < 0.001), Q max 14.36 ± 2.82 ml/s increased to 15.94 ± 2.71 ml/s (p = 0.032), while the Q ave did not change (p = 0.17). The number of urinations decreased from 13 (6 - 19) times to 10 (6 - 14) times (p <0.001).Conclusion. The study demonstrated the promise of PMN in men with LUTS in terms of improving the quality of life. The proposed method may be preferable for patients dissatisfied with drug therapy. Further placebo-controlled studies are required to help determine the role of PMN in the management of patients with LUTS.